Utilization of Cabbage Fermentation (Sauerkraut) as a Probiotic Source to Increase Pekin Duck Productivity - Haryadi, Haryadi; Husna, Asmaul; Rahmadhani, Nia (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2026)
The ban on antibiotic growth promoter (AGP) use has encouraged the development of natural probiotics to improve poultry performance, making it necessary to evaluate the potential of sauerkraut as a probiotic. The objective of this study was to determine the benefits of cabbage fermentation (sauerkraut) as a probiotic source to improve the productivity and meat quality of Pekin ducks. This study used a Completely Randomized Design (CRD) with five levels of sauerkraut probiotic doses in drinking water and four replications for each treatment. The treatments consisted of A (0%), B (1.5%), C (3%), D (4.5%), and E (6%) probiotic sauerkraut in ducks drinking water. The sauerkraut probiotic was produced through cabbage fermentation for seven days under anaerobic conditions. The observed parameters included body weight gain, feed intake, feed conversion ratio, carcass weight and meat quality (pH, water holding capacity and cooking loss). The data obtained were analyzed using Analysis of Variance and continued with Duncan’s Multiple Range Test to determine the significance of the differences among treatments. The results showed that the addition of sauerkraut probiotic in the drinking water of Pekin ducks had a significant effect (P<0.05) on body weight gain, feed intake, feed conversion ratio and carcass weight. However, a non significant effect (P>0.05) was observed on meat quality parameters (pH, water holding capacity and cooking loss). It was concluded that the addition of sauerkraut probiotics at the 4.5% level (Treatment D) was the optimal dose. It was able to improve productivity, with body weight gain of 1733.15 g, feed intake of 3848.30 g, a feed conversion ratio of 2.22, and carcass weight reaching 1299.86 g, without giving negative effects on the meat quality of Pekin ducks, with a meat pH of 6.25, water-holding capacity of 45.55% and cooking loss of 34.61%.